1989
DOI: 10.2169/internalmedicine1962.28.616
|View full text |Cite
|
Sign up to set email alerts
|

A case of cushing's disease and multiple myeloma.

Abstract: A 55-year-old female of Cushing's disease associated with multiple myeloma is reported. The association of the two diseases has not been previously noted. Elevated cortisol level was controlled successfully by low doses of adrenocorticolytic agent, o,p'-DDD. However, the exacerbation of multiple myelomawas found to accompanythe serum cortisol normalization. Previous reports have shown the good efficacy of combination therapy with melphalan and prednisolone for multiple myeloma. It was suggested that the decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…A literature review revealed that only two cases of MM with CS had been reported; in our case, however, there were some marked differences in the clinical manifestations compared with those reports [ 5 , 6 ]. Table 2 tabulates the previously published series of MM concomitant with CS.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…A literature review revealed that only two cases of MM with CS had been reported; in our case, however, there were some marked differences in the clinical manifestations compared with those reports [ 5 , 6 ]. Table 2 tabulates the previously published series of MM concomitant with CS.…”
Section: Discussioncontrasting
confidence: 72%
“…Kinugawa et al reported a case of Cushing disease (CD) and MM [ 5 ]. The clinical features were a rounded face, central obesity, and hypertension, so CS was suspected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that lymphoma progression was suppressed by the coexistent steroid‐producing adrenal tumour. The decision to treat the non‐Hodgkin's lymphoma was, in part, based on reports of progression of haematological disease following treatment of Cushing's syndrome 1 , 2 . Although histopathological examination of the tumour revealed some features suggestive of adrenocortical carcinoma, the distinction between adenoma and carcinoma can be difficult.…”
Section: Boxmentioning
confidence: 99%